The Predictive Study on Soweto Wind Turbine Results and Port-Elizabeth - Sithole, Tshepo; Veeredhi, Vasudeva Rao; Sithebe, Thembelani (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2023)
The results achieved for the research objectives of the Soweto Wind Turbine project were very encouraging. During comparison of prototype energy delivered versus time of day/month, results showed the energy production of Prototypes 1, 2 and 3 per month during operation at Soweto. It was observed that Prototype 3 outclassed Prototype 1 and 2 in terms of energy generated per month. Prototype 3 achieved 39.5 W output per wind speed of 1.17 m/s and was predicated to generate a maximum 40 kWh per month. Following information can be found in my recent published article, Implementation and Evaluation of a Low Speed and Self-Regulating Small Wind Turbine for Urban Areas in South Africa published at Engineering, Technology and Applied Science Research [ETASR] peer review open journal. This paper will present results on a predictive study which was subsequently done on implementing the same technology in the coastal regions of South Africa such as Gqeberha (formerly Port Elizabeth), where prevailing winds are much stronger. The results showed that, utilizing the empirically obtained data in Soweto, projected an energy output of up to 54.3 W per wind speed of 5.16 m/s (18.6 km/h) and up to 100 kWh per-month.